Wittgenstein as philosophical tone-poet : philosophy and music in dialogue - Szabados, Béla, 1942- (Studien zur Österreichischen Philosophie, 2014)
This book provides the first in-depth exploration of the importance of music for Ludwig Wittgenstein's life and work. Wittgenstein's remarks on music are essential for understanding his philosophy: they are on the nature of musical understanding, the relation of music to language, the concepts of representation and expression, on melody, irony and aspect-perception, and, on the great composers belonging to the Austrian-German tradition. Biography and philosophy, this work suggests that Wittgenstein was a composer of philosophy who used the musical form as a blueprint for his own writing and thought. For Wittgenstein music is not alone, but connects and resonates with our cultural forms of life. His relation to composers, especially to Richard Wagner and Gustav Mahler, enables Wittgenstein to address the question of how to do philosophy and compose music in the breakdown of tradition. Unlike his conservative musical sensibility, Wittgenstein's philosophy is open to musical experiments. Reflecting on his remarks on music makes it possible to compare the therapeutic aim of his philosophical activity with that of music, and thus notice affinities between Wittgenstein and John Cage.